Educational Intervention on Character Gradation of Digital Muslim Adolescents According to Al-Qur'an Surah Adz-Dzariyat Verse 56. - Yeni Insyirah; Muthoifin muthoifin; Triono Ali Mustofa (At-Ta'dib, 2023)
Education is the recognition of the truth that carried out by individuals, especially adolescent through formal, non-formal education and learning activities. The educational process that has the most influence on individual adolescents is the family, school, and community. The target of a life-long noble life can be achieved if Muslim youths able to get education that is right, appropriate, and in accordance with Islamic law so that all the knowledge they acquire always applies and maintains good morals which in the world of education are known as noble character. Guidance and training activities that take place inside and outside educational institutions play a role in accommodating the experiences of programmed Moslem adolescent aimed at optimizing self-efficacy appropriately. The basic problem in education that able to intervene in the formation of the character of young Muslims in the all-digital era like today is digitalization itself. This fundamental problem of digitalization will determine how Muslim adolescents will be in the future. Right and appropriate character education is very important to be applied in the lives of modern Muslim adolescents to find identity, overcome emotional instability, as well as anxiety and instability in asserting what is the chosen principle of life. This research is a scientific work which presents a discussion with reference to the library research method. The research object uses library data in the form of books as a data source, the holy book of the Koran surah adz-Dzariyat verse 56, and the subjectof the case is digital Muslim adolescent. The purpose of this research is to find educational interventions in shaping the character of the millennial Muslim generation who are actively involved in digitalization and are responsible as God-fearing servants in the perspective of the Qur’an surah adz-Dzariyat verse 56.